Competencias laborales del auditor de servicios de salud: un análisis funcional Venezuela, 2008. - Chirinos-Muñoz, Mónica S. (Revista de Salud Pública)
Objectives Using functional analysis for identifying the basic, working, specific and generic skil ls and values which a health service auditor must have. Methods Implementing the functional analysis technique with 10 experts, identifying specific, basic, generic skills and values by means of deductive logic. Results A functional map was obtained which started by establishing a key purpose based on improving healthcare and service quality from which three key functions emerged. The main functions and skills' units were then broken down into the competitive elements defining what a health service auditor is able to do. Discussion This functional map (following functional analysis methodology) shows in detail the simple and complex tasks which a healthcare auditor should apply in the workplace, adopting a forward management approach for improving heal thcare and health service quality. This methodology , expressing logical-deductive awareness raising, provides expert consensual information validating each element regarding overall skills.